Processing to valorise green biomass side streams to create new food ingredients - Phillips, Jade B. (2019)
The aim of the work presented in this thesis was to investigate differing conversion routes on pea biomass in order to make it a functional food ingredient with differing properties than it has in its native form. These would then have differing microstructures and properties to enable the pea biomass to have alternative structures and functions, which mirror starch functions. These modifications were made to formulate a powder-like material similar to that of a flour and to make a dispersion with added fibre, which is to be used within a composite model system. Thereby replacing a high calorific ingredient with a zero digested calorific one.